Manajemen Risiko dan Mitigasinya (Studi Pada Badan Amil Zakat Nasional Provinsi Gorontalo) - Muhibbuddin Muhibbuddin (Al-Buhuts, 2020)
This research was conducted with a view to the importance of implementation of risk management at the Agency which manages the zakat. Management of zakat is not far from the possibility of the occurrence of the risks that can lead to suboptimal management of zakat on the Agency management of zakat. This research was conducted in the BAZNAS in Gorontalo province. The purpose of this study is to (1) identify the risk management of zakat and its impact on BAZNAS in Gorontalo province, (2) to formulate the necessary efforts for mitigation of risk in BAZNAS in Gorontalo province. The method used a descriptive qualitative, this research uses a risk management process 5 of ISO 31000: 2009, namely communication and consultation, risk assessment (risk identification, risk analysis, risk evaluation), risk treatment, and monitoring and review. In this study a total of risk indentified by as much as 66 risks, risks are divided into 15 categories in risk group 4 types of risk. Those risks are firstly, reputation and risk losing muzakki is 9 risks, Second, the risk of channeling risk are 14. Third, the operational risk by as much as 41 risks, and fourth, transfer risk among countries is 2 risks. Each level of risk identified divided into 4 area, those are Very High, High, Medium and Low. On the territory of Very High risk indetified was only one, then for the high risk there are 18, while there are 39 risks in territory of Medium risk and territory of Low risk was 8 risk. For mitigation is recommended to divide the risk on Very High area, avoiding the risk of High area, reduce the risk in the Medium area, and accept the risk in the Low area.